The academic background of gerontologists and client satisfaction in long-term residential care for older persons. Issue 2 (1st February 2017) - Falcão, Ana; Pereira, Fernando; Pimentel, Helena; Teixeira, Cristina; Rodrigues, Vitor
ABSTRACT: In contemporary Western societies, the aging population poses new challenges both to the policies and to the support systems for older persons. In Portugal, where the phenomena have a major impact, a new professional profile, the gerontologist, has emerged. These professionals have an academic background that corresponds to the 1st cycle degree at Higher Schools and is specifically oriented to the care of older persons. This study aimed to analyze the performance of the gerontologist as a Long-term Residential Care (LRTC) manager in comparison to other professionals. A total of 160 older persons living in Portuguese LRTCs were questioned about their satisfaction in regard to the effectiveness of organization, environmental/structural factors, empathy with employees, occupational activities, and participation in the decision-making process. The client's satisfaction questionnaire covered 30 items, and each item was rated on a 5-point Likert scale. The older persons were classified as less satisfied or more satisfied according to the median value of the scale score. The older persons from LTRCs managed by a gerontologist are more likely to be more satisfied with provided care. This association was not explained by residents' characteristics nor by the older persons' circumstances as residents. These findings highlight the appropriateness of gerontologist skills in managing LTRCs.